PRO-OXIDANT-ANTIOXIDANT HOMEOSTASIS IN BOARS’ SPERM UNDER THE INFLUENCE OF DIFFERENT FEED ADDITIVES - Shostya, A. M.; Siabro, A. S.; Kovalchuk, I. I.; Krasnoshchok О. О.; Chukhlib, Ye. V.; Bereznytskyi, V. I. (Scientific Progress & Innovations, 2021)
The development of oxidative stress is one of the main reasons for reduced fertility of boars. This is due to the limited antioxidant capacity of spermatozoids to inhibit the generation of active oxygen forms, which makes them vulnerable to changes in pro-oxidant-antioxidant homeostasis in the body. The aim of the study was to research the effect of copper citrate and drone larvae homogenate on sperm quality and the formation of pro-oxidant-antioxidant homeostasis in breeding boars’ sperm. In the experiment, 9 adult boars of the Large White breed were used, the analogues in age, live weight and quality of sperm, from which 3 groups of animals 3 in each were formed. Experimental boars of group II received copper citrate (5%) in addition to the main diet, and animals of group III received the complex of copper citrate (5 %) with the homogenate of drone larvae. It was found that the introduction of copper citrate into the diet contributes to a probable increase in ejaculate mass (p<0.001), total spermatozoa’ amount (p<0.01) and their live forms (p<0.001). Such changes occur due to a decrease in the content of diene conjugates and TBA-active compounds in sperm by 20.1 % and 8.3 %, respectively, with a simultaneous decrease in the activity of superoxide dismutase by 19.1 % and catalase by 24.6 %, which indicates at slowing down peroxidation processes. Additional feeding of copper citrate (5 %) in combination with drone larvae homogenate, on the 45th day of feeding, probably increases the ejaculate weight (p<0.001), the number of live spermatozoa (p<0.001) and their survival ability (p<0.05). The eating of this complex supplement by breeding boars intensifies the processes of peroxidation in sperm – increases the concentration of diene conjugates by 17.1 % (on the 30th day) and 20.5 % (on the 45th day), and increases the content of TBA-active compounds in pro-oxidant poiser, which is accompanied by a decrease in superoxide dismutase activity (p<0.05). Such changes occur against the background of the maximum level of motility and survival ability of spermatozoa. Thus, the feeding of copper citrate (5 %) in the combination with the homogenate of drone larvae helps to increase the functional activity of spermatozoa by optimizing the formation of pro-oxidant-antioxidant homeostasis.